Rapid ATM-dependent phosphorylation of MDM2 precedes p53 accumulation in response to DNA damage - Khosravi, Rami (The National Academy of Sciences, 1999)
The p53 tumor-suppressor protein, a key regulator of cellular responses to genotoxic stress, is stabilized and activated after DNA damage. This process is associated with posttranslational modifications of p53, some of which are mediated by the ATM protein kinase. However, these modifications alone may not account in full for p53 stabilization. p53's stability and activity are negatively regulated by the oncoprotein MDM2, whose gene is activated by p53. Conceivably, p53 function may be modulated by modifications of MDM2 as well. We show here that after treatment of cells with ionizing radiation or a radiomimetic chemical, but not UV radiation, MDM2 is phosphorylated rapidly in an ATM-dependent manner. This phosphorylation is independent of p53 and the DNA-dependent protein kinase. Furthermore, MDM2 is directly phosphorylated by ATM in vitro. These findings suggest that in response to DNA strand breaks, ATM may promote p53 activity and stability by mediating simultaneous phosphorylation of both partners of the p53-MDM2 autoregulatory feedback loop.